Adoption and factors affecting on adoption of integrated pest management among vegetable farmers in Sri Lanka - Jayasooriya, H.J.C.; Aheeyar, Mohamed M. M. (Elsevier, 2016)
The overuse and misuse of chemical pesticides has widely been reported in vegetable cultivation in Sri Lanka. While safer and environmental friendly pest and disease management methods such as Integrated Pest Management (IPM) are popular around the world, only little effort has been taken to promote IPM in Sri Lankan vegetable cultivation. Furthermore, farmers have not shown much interest on practicing IPM in vegetable cultivation. However, the level of IPM adoption by vegetable farmers and the factors influencing the adoption and strategies to promote IPM in vegetable cultivation have not been identified. Accordingly, this study was conducted to identify the level of IPM adoption and factors influencing the adoption of IPM in vegetable cultivation and to understand the strategies for promoting vegetable IPM in future. Primary data was collected by interviewing 290 farmer households. ‘Level of adoption’ and ‘farmers’ knowledge’ on nine practices used in IPM technique were tested and nine socio-economic variables were analyzed to identify the factors influencing the IPM adoption. Findings indicated that the main income source of the majority (68%) of respondents was from vegetable farming from which at least half of their household income was secured. A total of 47% farmers apply chemical pesticides before pests or diseases appear in the field as a routine activity, and without considering the ‘economic threshold level’. Although the majority (60%) of farmers have used the recommended dosage in spraying, mixing several pesticides when applying was common. According to the findings, although the term IPM was familiar to 44% of respondents, only 20% s had a certain level of understanding on the IPM technique. The adoption of IPM practices among farmers was not at a satisfactory level. Practices known and followed for a long time were better adopted compared to the practices which are relatively novel. Results also showed that despite the adoption of these practices, understanding of farmers regarding the benefits and the appropriate use of such practices was not at a satisfactory level. “Farmers’ knowledge on IPM” had a positive impact while the “proportionate income from vegetable cultivation” was negative on the level of IPM adoption. In addition, the results showed that gaps in policy and institutional setup, negative attitudes of farmers and officers on IPM were conduce for the lower adoption level of IPM in the vegetable cultivation.